“Une grâce, une modestie, un sérieux”: The Reforming Neo-Classicism of Sedaine’s Philosophe sans le savoir - Gamble, D.R. (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
The objective of this article is to explain how Michel-Jean Sedaine’s play Le Philosophe sans le savoir (1765), considered the most successful example of the drame bourgeois, is characterised not only by the theatrical innovations advocated by Diderot in his writing on drama, but by central aspects of the reforming aesthetic movement that dominated the last half of the eighteenth century, and which has come to be known as neo-classicism.